웹툰 <화산귀환> 주인공 개성화 과정 연구 - 임소영 (스마트미디어저널, 2023)
This study analyzed the consciousness, unconsciousness, and individuation process of 'Cheongmyeong', the protagonist presented in the webtoon "Return of the Blossoming Blade", based on Jung's theory of individuation. The subject of the research was the webtoon "Return of the Blossoming Blade", which has formed a readership across various genders and age groups, based on a successful web novel. The individuation process of the protagonist of "Return of the Blossoming Blade", analyzed using Jung's theory, is as follows: Firstly, the protagonist's ego originated from the shadow derived from the unconscious. Secondly, the protagonist's persona is social and positive in reality, but the personal persona manifested as an unrevealed shadow. Thirdly, the protagonist's anima/animus connects the profound inner consciousness with reality, maintaining a complementary relationship with the persona. Fourthly, the protagonist's Self symbolizes the collective ideal human and the essence of the volcano. The protagonist was shown to achieve individuation through a continuous repetitive process of integrating consciousness and unconsciousness, and through the compensatory process. 이 연구는 웹툰 <화산귀환>을 통해 제시되는 주인공 '청명'의 의식과 무의식, 개성화 과정을 융의 개성화 과정 이론에 접목하여 분석하였다. 연구 대상은 성공한 웹소설을 기반으로 다양한 성별과 연령대의 독자층을 형성하고 있는 웹툰 <화산귀환>을 선정하였다. 융의 개성화 과정 이론에 접목하여 분석한 <화산귀환> 주인공의 개성화 과정은 첫째, 주인공의 자아는 무의식에서 파생된 그림자로부터 발생하였다. 둘째, 주인공의 페르소나는 현실에서는 사회적이며 긍정적이지만, 개인적인 페르소나는 드러낼 수 없는 그림자로 나타났다. 셋째, 주인공의 아니마/무스는 깊은 의식 내면과 현실을 연결하며, 페르소나와 보완적 관계에 있다. 넷째, 주인공의 자기(Self)는 총체적인 이상적인 인간과 화산의 근본을 상징한다. 주인공은 끊임없이 반복적으로 의식과 무의식의 통합과정을 거치면서 보상받는 과정에서 자기실현이 이루어지는 것으로 나타났다.